Potentials, Subsidies and Tradeoffs of Cellulosic Ethanol in the European Union - Franziska Schuenemann; Ruth Delzeit (Ecological Economics, 2022)
The EU's revised Renewable Energy Directive (RED2) sets high mandates for advanced biofuels like cellulosic bioethanol from agricultural residues. However, many residues are used for ecological and economic purposes such as soil organic carbon regulation and livestock bedding and fodder. We use the global CGE model DART-BIO with a detailed representation of the bioeconomy to simulate the RED2 cellulosic bioethanol mandates and run sensitivity analyses regarding processing technology, straw and oil prices. We implement a latent cellulosic ethanol technology and develop new sectors for agricultural residues. We find that the RED2 cellulosic ethanol mandates will require enormous amounts of residues that could exceed the sustainable available potential in the EU. Agricultural residue utilization changes substantially and the cellulosic ethanol industry becomes the main residue consumer. Results show that output and price impacts of advanced biofuel targets are small, but there is reallocation of land towards cereals that enter the agricultural residue sector away from other crops in the EU. Moreover, the size of necessary cellulosic ethanol subsidies and the abatement costs per tonCO2eq are very sensitive to actual straw and oil prices.
Keywords: 330; Agricultural residues; Advanced biofuels; Cellulosic ethanol; Bioeconomy; CGE model